The morality of reproductive cloning from theperspective of utilitarian philosophy - Beraún-Barrantes, José Antonio (2020)
The concept of reproductive cloning refers to the possibility of being able to offspring through the use of technology, except that it is our own genes that are used to carry it out. The problem faced by this type of assisted reproduction technique is that of morality or immorality. In order to better determine whether it is viable or not, a general analysis is made from the perspective of utilitarian philosophy. This article argues that the morality surrounding the reproductive cloning technique does not violate the foundations of human dignity. It addresses the issue of Arrow's paradox and the concept of domain restriction is proposed as a theoretical framework for the solution of this paradox.